FEMINISME : SEBUAH KOMUNIKASI SPIRITUALITAS MENUJU PENGUATAN SISTEM SOSIAL - Surahman Cinu Surahman (Kinesik, 2021)
Discourse on feminism can be seen in the struggle of a woman named Hajar. As the mother of the Prophets, Hajar helped support the foundation of civilization framed by Ismail, her son, as a form of social movement wrapped in spiritual awareness, that all forms of racism, feudalism and domination of capital, will disappear in the power of God. This is enshrined in the Hajj ritual, jogging between the hills of Safa and Marwah. Hajar is a historical cultural capital that is represented from class consciousness, which must be accumulated for future civilizations. That is why in an effort to explore these events, the meaning of symbols is needed, according to the model used in history. Meanwhile, the German female philosopher, Hannah Arendt said that there was an important change in the map of human civilization as a result of the 19th century European spirit which eroded and destroyed the structure of the nation's self, regarding the nation state. He highlighted the racism and imperialism of the century which combined a number of forces that were destructive to the public spheres of explanation for their own sake. Ironically, Indonesian women are actually indoctrinated that Western women's traditions are the best. This paper offers how the trend of feminism in Indonesia.